Dystrophic neurites accumulating autophagic vacuoles show early stages of neuritic destruction - Liberski, Paweł P.; Gajos, Agata; Sikorska, Beata (Folia Neuropathologica, 2018)
We re-examined the database of some 20,000 electron micrographs from the Echigo-1, the 263K-strain or the 22C-H of scrapie-infected hamsters to look for the cytoplasmic clearance. We reevaluated the largest database in the world of photographed dystrophic neurites for the presence of cytoplasmic clearance as shown in transgenic fruit flies transfected with A-42. In several neurites, we found electron-lucent areas not bound by any membranes or only partially bound; thus, they were not autophagic vacuoles as the latter are membrane-bound and contain cargo. Those changes were not observed in every examined neurite and no correlation with any other changes were noticed. In some neurites, which could be traced over several sections, the electron-lucent areas were evident to change size, i.e. to expand.